Results of External Beam Parametrial Boost for Advanced Cervical Cancer - Mauro, Geovanne Pedro; Najas, Gabriel Faria; Poço, João Guilherme Eiras; Kleine, Rodolpho Truffa; Carvalho, Heloisa de Andrade (Brazilian Journal of Oncology, 2025)
Introduction Even though largely used, external beam parametrial boost concurrent with brachytherapy for advanced cervical cancer is consensual and lacks prospective evidence.Objective To assess the impact of external beam parametrial boost on cancer control and toxicity.Materials and Methods The present research is a retrospective, single, institutional study of patients with locally advanced cervical cancer with parametrial involvement.Results The charts of 247 patients with parametrial invasion treated with concurrent chemoradiation and brachytherapy were assessed. The mean follow-up was 48.2 months. Median overall survival (OS), local progression-free survival (LPFS), and distant progression-free survival (DPFS) were not reached. Overall survival, LPFS, and DPFS at 3 years were 81.4%, 87.4%, and 83.4%, respectively. The mean OS for patients receiving parametrial boost and those that did not receive was 47.4 months and 46.8 months, and the mean LPFS was 43.9 months and 44.0, respectively. There were no differences regarding acute (p = 0.662) or late (p = 0.923) toxicity between groups. There were 6 deaths due to treatment, all in the parametrial boost group.Conclusion External beam parametrial boost should be carefully and not routinely considered. There is a lack of good evidence on the matter, and prospective studies should be designed regarding parametrial boost, perhaps with interstitial brachytherapy and not external beam.
Keywords: brachytherapy; radiotherapy; uterine cervical neoplasms